Masseter Muscle Thickness and Maxillofacial Morphology - A Pilot Study - Aynur Medine Şahin-Sağlam; Alev Aksoy-Doğan; Meltem Çetin (Galenos Yayinevi, 2009)
The aim of this study was to investigate how the thickness of the masseter muscle relates to the maxillofacial morphology, including the thickness of alveolar process in the mandibular incisor region, and the thickness of the mandibular symphysis. The subjects consisted of 25 volunteers of whom consisted of 17 females and 8 males (mean age: 21 years 3 months). The relationship between masseter muscle thickness and the maxillofacial skeleton was investigated by measuring the former by ultrasonograpy and the latter by roentgenographic cephalometry. Five angular and ten linear measurements were traced. The data were analysed using multiple regression analysis. According to the present study, the masseter muscle thickness was 9.7±1.6mm in the relaxed state and 12.5±1.7mm during clenching. The results of the multiple regression analysis showed that masseter muscle thickness in the clenching state was only significantly correlated with the "ramus inclination to SN" angle (p<0.05). Therefore it is suggested that the limited masticatory forces dont influence the maxillofacial morphology.